Analisis Sosiologi Hukum Terhadap Putusan Mahkamah Konstitusi Nomor 90/PUU-XII/2023 : Legitimasi Kekuasaan Dan Dinamika Sosial Di Indonesia - Noman Tuboinam Waruwu; Rosmalinda; Agusmidah (Case Law : Journal of Law, 2026)
The Constitutional Court is a state institution exercising independent judicial power to administer justice to uphold law and justice, whose decisions are final and binding. This study conducts an in-depth analysis of the Constitutional Court Decision Number 90/PUU-XII/2023 by applying a sociological perspective of law based on the theory of legal realism. The main focus of this study is to uncover how the legitimacy of power and the social dynamics that arise from the determination of the age limit for presidential/vice presidential candidates influence. This study uses a socio-legal methodology (socio-legal research) or a combined normative-empirical legal research that is descriptive-analytical in nature with the aim of describing the content of the decision and the social dynamics that arise, then analyzing the relationship between the two using the theories of legal realism and legal sociology. The results of the study indicate that the Constitutional Court Decision Number 90/PUU-XII/2023 is not merely the result of pure legal deduction, but is more significantly influenced by political interests outside the official legal framework (extra-legal), and creates social divisions (polarization), because it is considered to smooth the interests of those in power. Therefore, the study concludes that judicial independence is a crucial and fundamental element in maintaining the dignity and honor of the courts and achieving justice, certainty, and the benefit of the law. Keywords: Sociology of Law, Legitimacy of Power, Social Dynamics.